La responsabilidad social empresarial en el proceso del cultivo de banano y su incidencia en el nivel de vida de la población del sector el desquite del cantón Quevedo, periodo 2009-2014 - Arce Quintana, Byron Ruddy (2015)
The present research on Corporate “SOCIAL RESPONSIBILITY IN THE PROCESS OF BANANA CULTIVATION AND ITS IMPACT ON THE STANDARD OF LIVING OF THE POPULATION OF THE SECTOR'S DESQUITE, QUEVEDO CANTON, 2009- 2014”. Has the main objective of describing the importance of the economic and environmental impact of plantations of banana cultivation through corporate social responsibility and administrative operations of the companies that are posesionadas in the sector. The theoretical foundation on which this study theories and thinking about environmental economics, also corporate social responsibility in international countries, the operationalization of companies, types of externalities, environmental, economic, living standards of the population is based , their concepts and relevant legal bases. In addition the results of the investigation was derived based on surveys of residents and workers, the interview was conducted at the Editor's operational area and a worker process of banana cultivation, through this study was conducted the direct observation of the population of the sector, thus achieving obtain the information necessary for the respective "Corporate social responsibility in the process of banana cultivation affects the standard of living of the population of the sector," the Recovery " Quevedo canton period 2009-2014 "the same as determined through research techniques The findings discussed were: The results of the research evidence, the existence of environmental pollution through the spraying of plantations of banana cultivation, as the operational area possesses no suitable equipment and streamlining environmental mitigation strategies, causing instability the population.